A Woman's Worth: the Story of the Ford Sewing Machinists (2006)
2006 "A Woman's Worth: the Story of the Ford Sewing Machinists", 2006, Boston, Sarah Read the Notes by Sue Hastings (below) to learn more about the background to the film.